GPR115 Contributes to Lung Adenocarcinoma Metastasis Associated With LAMC2 and Predicts a Poor Prognosis - Wang, Yingjing; Shi, Muqi; Yang, Nan; Zhou, Xiaoyu; Xu, Liqin (Frontiers in Oncology, 2020)
GPR115, a member of the adhesion G protein-coupled receptor family, is dysregulated in many cancers. However, the expression and function of GRP115 in non-small cell lung cancer (NSCLC) is not clear. Here, we examined the expression pattern, clinical significance, and function of GPR115 in NSCLC by analysis of clinical specimens and human cell lines and bioinformatics analysis. Immunohistochemical analysis of clinical samples showed that GPR115 was significantly upregulated in NSCLC tissues compares with normal lung epithelial tissue (P<0.05). And GPR115 overexpression is an independent prognostic factor for 5-year overall survival of NSCLC patients [hazard ratio (HR)=1.625, P=0.008]. And higher expression of GPR115 was strongly correlation with differentiation level (P=0.027), tumor size (P=0.010), lymph node metastasis (P=0.022), tumor-node-metastasis stage (P=0.008) and poor prognosis of lung adenocarcinoma (LUAD, all P=0.039), but not lung squamous cell carcinoma (LUSC, P>0.05). Moreover, downregulation of GPR115 by RNA interference in human lung cancer lines inhibited cell proliferation, migration, and invasion. Preliminary bioinformatic analysis confirmed that GPR115 was closely associated with LAMC2 (Spearman correlation coefficient=0.67, P<0.05), which was accumulated in ECM-receptor interaction and focal adhesion. Consistent with these findings, deceased of GPR115 was associated with E-cadherin, N-cadherin and Vimentin confirmed by western blot. In conclusion, these data suggest that GPR115 may play a role in the tumor growth and metastasis and may have utility as a diagnostic and prognostic marker for LUAD.